Government incentives facing COVID-19: A comparative study between Brazil and Chile in light of communication theory - Jamille Carla Oliveira Araújo; Fernando Gentil de Souza; Agostinha Patrícia da Silva Gomes (Contabilidad y Negocios: Revista del Departamento Académico de Ciencias Administrativas, 2023)
The COVID-19 pandemic forced different countries to implement new strategies to reduce its spread and mitigate its economic and social effects. Given this scenario, this study aims to compare government incentives granted by Brazil and Chile, in response to the economic effects of COVID-19. This qualitative and exploratory research uses indirect (bibliographic) and secondary documentation with data collected from the websites of the state governments in each country, between 2020 and 2021. The Iramuteq 2.0 software for data analysis. Based on Factorial Correspondence Analysis using a dendrogram, the study analyzes the incentives launched by: laws, decrees, contingency policies, guidelines in booklets, applications, and combating fake news, classified into 4 (four) categories: (i) tax and labor, (ii) actions on social networks, (iii) benefits programs and (iv) legalization. The results show that Chile offered more incentives than Brazil, highlighting the helping program from large companies to small ones, On the other hand, Brazil conducted more campaigns to combat fake news. In the light of the communication theory (CT), the findings highlighted the advances of governments in the expansion of digital channels (social networks, web pages and applications) to inform citizens and companies. During this period State Governments learned new insights to outline new strategies to stimulate the economy, to promote learning and increase the capacity to lead in contexts of crises and pandemic